2016
DOI: 10.18632/oncotarget.13219
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of USP33 in advanced colorectal cancer patients: new insights into β-arrestin-dependent ERK signaling

Abstract: Patients with liver metastases of colorectal cancer (CRCLM) have a poorer prognosis compared to colorectal cancer (CRC) patients in local stage. Evaluating the recurrence and overall survival of advanced patients is critical in improving disease treatment and clinical outcome. Here we investigated the expression pattern of USP33, a deubiquitinating enzyme, in both primary CRC tissues and liver metastases tissues. Univariate and multivariate analyses identified that low expression of USP33 in CRCLM tissues indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…Total RNA was isolated from left ventricular tissues with Trizol reagent (Invitrogen, CA, USA) following manufacturer's instructions. Concentration of total RNA was estimated, and the qRT-PCR was conducted as described by others (Liu et al 2016). The primer sequences are shown in Table 1.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Total RNA was isolated from left ventricular tissues with Trizol reagent (Invitrogen, CA, USA) following manufacturer's instructions. Concentration of total RNA was estimated, and the qRT-PCR was conducted as described by others (Liu et al 2016). The primer sequences are shown in Table 1.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Consequently, various protein enzymes are drawing more and more attentions, including kinases (Jung et al 2016), phosphatases (Rajadurai and Havrylov 2016), ubiquitin ligases (Signoretti et al 2016) and deubiquitinases (Liu et al 2016). However, either the process of protein expression or modification needs energy; thus, energy dysregulation plays important roles in carcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ubiquitin-specific protease 33 (USP33) was shown to be down-regulated in breast cancer (YuasaKawada et al 2009), lung cancer (Wen et al 2014) and colorectal cancer (Liu et al 2016b). On the other hand, we previously reported the enhanced expression of ubiquitinspecific protease 7 (USP7) in ovarian cancer (Ma and Yu 2016), which revealed that different ubiquitin-regulated enzymes may show completely different functions in tumor regulation.…”
Section: Introductionmentioning
confidence: 99%